(untitled) (Journal of Information Systems and Technology Management, 2005)
Since the sprouting of the informantion technology (IT) and its use for the companies the relation between cost and benefit did not stay clear. This is a question that has been studied and analyzed in depth in the academic and organizacional environments. The results of the studies point with respect to two opposing sides: first, one believes that IT does not pass of a tool without strategical value. On the order side, enterprises work with idea thar IT is strategic solution for many problems for all levels and businesses. Beyond this paradox, the challenge exists to justify the high investiments in technology, since the companies, ahead of the high competitiveness the enterprises could not focus in efforts no productives. The theoretical paper does not intend to answer the question, but to only describe the aspects that lead to such doubt. For such, it describes some concepts of IT, the IT business value, analysis of he investmensts in IT and IT as a commodity. At the final, are presented the limitations of this theoretical reflection and the expositons on the concepts and of its difficult practical applicability.